Primary health care in rural Malawi - a qualitative assessment exploring the relevance of the community-directed interventions approach - Makaula Peter; Bloch Paul; Banda Hastings T; Mbera Grace Bongololo; Mangani Charles; de Sousa Alexandra; Nkhono Edwin; Jemu Samuel; Muula Adamson S (BMC, 2012)
Abstract Background Primary Health Care (PHC) is a strategy endorsed for attaining equitable access to basic health care including treatment and prevention of endemic diseases. Thirty four years later, its implementation remains sub-optimal in most Sub-Saharan African countries that access to health interventions is still a major challenge for a large proportion of the rural population. Community-directed treatment with ivermectin (CDTi) and community-directed interventions (CDI) are participatory approaches to strengthen health care at community level. Both approaches are based on values and principles associated with PHC. The CDI approach has successfully been used to improve the delivery of interventions in areas that have previously used CDTi. However, little is known about the added value of community participation in areas without prior experience with CDTi. This study aimed at assessing PHC in two rural Malawian districts without CDTi experience with a view to explore the relevance of the CDI approach. We examined health service providers' and beneficiaries' perceptions on existing PHC practices, and their perspectives on official priorities and strategies to strengthen PHC. Methods We conducted 27 key informant interviews with health officials and partners at national, district and health centre levels; 32 focus group discussions with community members and in-depth interviews with 32 community members and 32 community leaders. Additionally, official PHC related documents were reviewed. Results The findings show that there is a functional PHC system in place in the two study districts, though its implementation is faced with various challenges related to accessibility of services and shortage of resources. Health service providers and consumers shared perceptions on the importance of intensifying community participation to strengthen PHC, particularly within the areas of provision of insecticide treated bed nets, home case management for malaria, management of diarrhoeal diseases, treatment of schistosomiasis and provision of food supplements against malnutrition. Conclusion Our study indicates that intensified community participation based on the CDI approach can be considered as a realistic means to increase accessibility of certain vital interventions at community level.